TANTANGAN ETIKA PROFESI GURU DI ERA DISRUPSI DIGITAL: PERSPEKTIF PEDAGOGIS DAN MORAL - Widhia Ningrum, Putri; Nafisah Arini, Bilqis; Akhsani, Wigati; Muhlisin, Muhlisin; Mafaakhir, Abul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital revolution has caused a major change in the education system, not only altering the tools used for teaching but also redefining the ethical boundaries of the teaching profession. This study aims to identify the ethical challenges faced by educators through two main perspectives: pedagogical and moral. This study uses a descriptive qualitative approach with a literature review to examine how the shift of a teacher's role from being an authority figure to a digital facilitator creates ethical ambiguity. Teachers face pressure to incorporate technology without losing the human aspect of interaction. The main challenges include the weakening of academic authority because of instant access to information and the difficulty of maintaining privacy and professionalism in the online world. Digital disruption has led to a crisis in role models. Teachers are needed to act as moral guides in a time when there is a lot of false information and online bullying, where the line between personal and professional life often becomes unclear. The conclusion of this study highlights the importance of rebuilding a teacher's code of ethics that is more flexible to the digital world, without losing the important teaching values. Strengthening digital literacy based on character is now a necessity for educators to maintain their professional integrity in the face of rapidly changing times.